Historical review of the fiscal system (publ. at the "Standard of Freedom" Office, 1850)
Contains section XVI(2nd part)-XX(1st part), continued from tract no. 31, to be continued in tract no. 33. - Issued by the Liverpool Financial Reform Association. - Authorship claimed by Alexander Somerville. - In pamphlet volume with covertitle: Tracts of the Liverpool Financial Reform Association.